2010
DOI: 10.1128/jcm.01312-09
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pyogenes Isolates Causing Severe Infections in Norway in 2006 to 2007: emm Types, Multilocus Sequence Types, and Superantigen Profiles

Abstract: To investigate the epidemiological patterns and genetic characteristics of disease caused by group A Streptococcus (GAS), all available isolates from invasive cases in Norway during 2006 to 2007 (262 isolates) were subjected to antimicrobial susceptibility testing, T serotyping, emm typing, and multilocus sequence typing and screened for known streptococcal pyrogenic exotoxin (Spe) genes, smeZ, and ssa. The average incidence rate was 3.1 cases per 100,000 individuals. The most prevalent sequence types (STs) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
44
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 57 publications
12
44
2
1
Order By: Relevance
“…36 Almost all M6 isolates studied in these reports were resistant to ofloxacin, while all other M types were susceptible. Another example of tight correlation between rare antibiotic resistance phenotypes and specific M types comes from a study in France which showed a unique resistance to bacitracin (paired with wide resistance to other diverse antibiotics) among M28 isolates.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 89%
See 3 more Smart Citations
“…36 Almost all M6 isolates studied in these reports were resistant to ofloxacin, while all other M types were susceptible. Another example of tight correlation between rare antibiotic resistance phenotypes and specific M types comes from a study in France which showed a unique resistance to bacitracin (paired with wide resistance to other diverse antibiotics) among M28 isolates.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 89%
“…Moreover, the types that are most dominant in invasive categories, and hence those responsible for the observed decrease in diversity, are almost always the same-most notably M1 and M3. 8,12,18,[32][33][34][35][36] Similar dynamics, including decreased diversity and the dominance of specific types, are apparent in studies of more specific clinical phenomena such as fatality, associated with M1, M3 and M12, 32 puerperal sepsis, associated with M28, 34,36,37 STSS, associated with M1 and M3, 12,35,38 epidemic ARF, associated with M5 and M18, 39 and geographically widespread epidemic behavior, most commonly associated with M1. 2,12 Despite genetic changes in these serotypes over time, including alterations of virulence and antibiotic resistance factors, these associations generally remain stable.…”
Section: Clinical Relevance Of M Typementioning
confidence: 93%
See 2 more Smart Citations
“…The M protein is encoded by the emm gene, and sequence analysis of the 59 hypervariable portion of this gene has largely replaced the serological typing method (Beall et al, 1996). The emm type distribution varies worldwide but emm types 1, 3, 28 and 89 are the most commonly found types in reports of GAS-related disease (Imöhl et al, 2010;Meisal et al, 2010a;Siljander et al, 2010).…”
Section: Introductionmentioning
confidence: 99%